Genomic analysis identified a potential novel molecular mechanism for high-altitude adaptation in sheep at the Himalayas - Gorkhali, N.A.; Kunzhe Dong; Min Yang; Shen Song; Kader, A.; Shrestha, B.S.; Xiaohong He; Qian-Jun Zhao; Yabin Pu; Xiangchen Li; Kijas, J.; Weijun, Guan; et al. (Springer, 2016)
Sheep has successfully adapted to the extreme high-altitude Himalayan region. To identify genes underlying such adaptation, we genotyped genome-wide single nucleotide polymorphisms (SNPs) of four major sheep breeds living at different altitudes in Nepal and downloaded SNP array data from additional Asian and Middle East breeds. Using a di value-based genomic comparison between four high-altitude and eight lowland Asian breeds, we discovered the most differentiated variants at the locus of FGF-7 (Keratinocyte growth factor-7), which was previously reported as a good protective candidate for pulmonary injuries. We further found a SNP upstream of FGF-7 that appears to contribute to the divergence signature. First, the SNP occurred at an extremely conserved site. Second, the SNP showed an increasing allele frequency with the elevated altitude in Nepalese sheep. Third, the electrophoretic mobility shift assays (EMSA) analysis using human lung cancer cells revealed the allele-specific DNA-protein interactions. We thus hypothesized that FGF-7 gene potentially enhances lung function by regulating its expression level in high-altitude sheep through altering its binding of specific transcription factors. Especially, FGF-7 gene was not implicated in previous studies of other high-altitude species, suggesting a potential novel adaptive mechanism to high altitude in sheep at the Himalayas.